The Transition Between Antiparallel and Component Magnetic Reconnection at Earth's Dayside Magnetopause. Issue 12 (28th December 2018) - Trattner, K. J.; Burch, J. L.; Cassak, P. A.; Ergun, R.; Eriksson, S.; Fuselier, S. A.; Giles, B. L.; Gomez, R. G.; Grimes, E. W.; Petrinec, S. M.; Webster, J. M.; Wilder, F. D.
Abstract: Magnetic reconnection at Earth's magnetopause is usually described by two different scenarios, antiparallel and component reconnection. The Maximum Magnetic Shear model combines these two scenarios at specific connection points known as the Knee regions. Using a database of confirmed magnetopause reconnection locations observed during Phase 1a of the Magnetospheric Multiscale mission, a recent study showed that the model predicts the reconnection locations correctly within 2 Earth radii 80% of the time. The study also revealed and confirmed the existence of anomalies, that is, a specific set of conditions/parameters for which the observed reconnection locations are significantly different than the predicted locations. The first anomaly, described in an earlier study, occurs during the equinoxes for events with interplanetary magnetic field (IMF) clock angles around 120° and 240°. Another previously unknown anomaly was found for events observed around December that also occurs for the same IMF clock angle ranges as the first anomaly. Several of the anomalous December events were observed in the dawn sector Knee region and show that a combination of a large dipole tilt with an IMF clock angle of about 140° causes the magnetopause antiparallel reconnection region to line up along the draped IMF. That causes a deflection of the Knee points and the predicted reconnection location. These events demonstrate that magnetic reconnection at the Earth's dayside magnetopause preferentially occurs in the antiparallel locations and only occurs along component reconnection line segments when the draped IMF field lines at the magnetopause no longer contact an antiparallel reconnection region. Key Points: Antiparallel magnetic reconnection is dominant at the Earths magnetopause Antiparallel magnetic reconnection seems to control where component reconnection will occur